Device For Determining Multi-Cycle Tensile Strain Of Knitted Fabrics (Pulsator) - D.X. Ubaydullayeva; N.R.Xanxadjyaeva; E.T.Laysheva; M.F Axmedova; Z.Yunusova; F.A.Maxamadova (Genius Journals, 2026)
The article discusses the need to create equipment for determining the multi-cycle tensile deformation of knitted fabrics and the possibility of a more complete analysis of the dimensional stability of knitted fabrics by determining it, as well as the creation of a special pulsation device for this purpose. The composition of the main parts of the pulsator device and its use, as well as a schematic and external drawing of the device, are given.
Keywords: single-cycle stretching; longitudinal; transverse